Membangun dan Mengembangkan Ekonomi Kreatif yaitu Kuliner Etnik Siantar melalui Festival Tapai Siantar - Nadila Erfiyana; Armitha Silalahi; Haney Eir Valensia Tarigan; Darwin Damanik (Jurnal Masyarakat Mengabdi Nusantara, 2022)
Tapai is Siantar ethnic food in the city of Pematang Siantar. However, tapai is very difficult to find because it does not have a special place to sell it. Tapai traders sell tapai while walking around the city of Pematang Siantar. The purpose of this activity to build a creative economy through culinary is to make tapai a home industry product that is of great interest to the people of the city of Pematang Siantar and visitors to the city of Pematang Siantar. This activity was carried out by students of the Stambuk 2020 Development Economics study program with the supporting lecturer Dian Purba SE, M.Sc in collaboration with the Pematang Siantar City Government, the Education and Teaching Office. This activity was held on Thursday, December 1, 2022 at the Faculty of Economics, Simalungun University. The method of carrying out this activity is by holding competitions for various variants of processed tapai which are participated in by SMA/SMK students from the city of Pematang Siantar. The number of participants in the competition is 10 teams consisting of 3 people for each team. The implementation of this activity is carried out with the aim of developing student creativity in terms of managing tapai.